Exosomal FABP5 drives HCC progression via macrophage lipid metabolism and immune microenvironment remodeling - Luo, Siyi; Tang, Rui; Jiang, Ling; Luo, Qichi; Fu, Junhao; Wu, Bo; Wang, Guowu (Frontiers in Immunology, 2025)
IntroductionThe progression of hepatocellular carcinoma (HCC) is intricately linked to complex interactions within the tumor microenvironment (TME), where the reprogramming of tumor-associated macrophages (TAMs) plays a pivotal role. However, how HCC cells regulate TAM metabolism and function via extracellular vesicles, such as exosomes, remains incompletely understood.MethodsWe isolated exosomes from HCC cell lines and co-cultured them with macrophages. Using proteomics, lipid analysis, flow cytometry, and animal models, we evaluated the effects of exosomal FABP5 on macrophage polarization and lipid metabolism. The role of FABP5 in tumor progression was assessed via in vivo experiments.ResultsThis study reveals that HCC cells release fatty acid-binding protein 5 (FABP5) via exosomes, transferring it to TAMs, thereby inducing significant lipid metabolism reprogramming in macrophages. Mechanistically, exosomal FABP5 promotes lipid accumulation by activating the PPARγ signaling pathway, while potentially inhibiting the PPARα signaling pathway to reduce fatty acid oxidation, ultimately driving TAM polarization towards an M2 phenotype, characterized by increased secretion of immunosuppressive cytokines and a pro-tumor phenotype. Clinical data analysis indicates that high FABP5 expression in HCC tissues correlates with poor patient prognosis. In liver-specific FABP5 knockout mouse models and HCC xenograft models, FABP5 deletion significantly suppressed tumor growth, reduced M2-type TAM infiltration and lipid accumulation, and enhanced anti-tumor immune responses.ConclusionThese findings collectively uncover exosomal FABP5 as a key mediator of metabolic and immune communication between HCC and TAMs, promoting HCC progression by remodeling the tumor immune microenvironment, and suggest FABP5 as a potential therapeutic target for HCC.